2013
DOI: 10.1145/2542182.2542195
|View full text |Cite
|
Sign up to set email alerts
|

Active learning strategies for rating elicitation in collaborative filtering

Abstract: The accuracy of collaborative-filtering recommender systems largely depends on three factors: the quality of the rating prediction algorithm, and the quantity and quality of available ratings. While research in the field of recommender systems often concentrates on improving prediction algorithms, even the best algorithms will fail if they are fed poor-quality data during training, that is, garbage in, garbage out. Active learning aims to remedy this problem by focusing on obtaining better-quality data that mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 35 publications
0
47
0
Order By: Relevance
“…Active Learning in RSs aims at actively acquiring user preference data to improve the output of the RS [21,7,6]. In [17] six techniques that collaborative filtering systems can use to learn about new users in the sign up process are introduced: entropy where items with the largest rating entropy are preferred; random; popularity; log(popularity) * entropy where items that are both popular and have diverse ratings are preferred; and finally item-item personalized, where the items are proposed randomly until one rating is acquired, then a recommender is used to predict the items that the user is likely to have seen.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Active Learning in RSs aims at actively acquiring user preference data to improve the output of the RS [21,7,6]. In [17] six techniques that collaborative filtering systems can use to learn about new users in the sign up process are introduced: entropy where items with the largest rating entropy are preferred; random; popularity; log(popularity) * entropy where items that are both popular and have diverse ratings are preferred; and finally item-item personalized, where the items are proposed randomly until one rating is acquired, then a recommender is used to predict the items that the user is likely to have seen.…”
Section: Related Workmentioning
confidence: 99%
“…Several approaches have been recently proposed to deal with this problem [20] but the most direct way is to rely on active learning (AL), i.e., to use an initial data acquisition and learning phase. Here the system actively asks the user to rate a set of items, which are identified using a strategy aimed at best revealing the user's interests and consequently at improving the quality of the recommendations [21,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, regardless of the specific variant that is used, CF methods have a common limitation: the so called new user cold-start problem, which occurs when a system cannot generate personalized and relevant recommendations for a user who has just registered into the system. Although many solutions have been proposed [23,24,33,56,58,72,47,69], this problem is still challenging, and there is not a unique solution for it that can be applied to any domain or situation. Indeed, as we shall show later, different approaches better suit specific situations, e.g., when the new user has entered either zero or only a few ratings.…”
Section: Introductionmentioning
confidence: 99%
“…In general, in AL it has been shown that asking a user to provide ratings for a set of selected items can improve the accuracy of CF [65,23,21,22,57,58]. Traditional active learning methods need some pre-existent ratings in order to select even more ratings to collect from the user.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation